(untitled) (Bangladesh Journal of Pharmacology, 2023)
This study aimed to explore the in vitro antibacterial potential of endophytic fungus isolated from the roots of Polianthes tuberosa against multidrug-resistant pathogens. Fungal isolates were screened for their antibacterial activities by disc diffusion, agar plug diffusion, MIC, and MBC method. GC-MS was carried out to determine the crude extract’s chemical profile. The highest antagonistic effect in the disc diffusion method was seen in the ethyl acetate extract of PTR3, with an inhibitory zone ranging from 14-18 mm. Therefore, the potent isolate was identified as Daldinia eschscholtzii. The maximum inhibition of 18 mm and 20 mm was observed against MRSA (ATCC 43300) (ATCC 700699), followed by VRE (14 mm). The MIC and MBC were between 3.12-25 μg/mL and 6.25-50 μg/mL, respectively. 1,2-Benzene dicarboxylic acid and diheptyl ester were the primary chemical constituents present in the extract. These findings confirm that D. eschscholtzii PTR3 crude extract shows antibacterial activity.